Nonparabolicity effects on electron-confined LO-phonon scattering rates in GaAs-Al₀.₄₅Ga₀.₅₅As superlattice - Abouelaoualim, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
We investigate theoretically the effect of nonparabolic band structure on the electron-confined LO-phonon scattering rate in GaAs-Al₀.₄₅Ga₀.₅₅As superlattice. Using the quantum treatment, the new wave function of electron miniband conduction of superlattice and a reformulation of the slab model for the confined LO-phonon modes has been considered. An expression for the scattering rates has been obtained. Our results show that, for transitions related to the emission of confined LO-phonon, the scattering rates are significantly increased in the band nonparabolicity case.